Ekspansi Pemasaran melalui Pembaharuan Packaging dan Marketing Sosial Media UMKM Kota Baru - Deni Sabriyanti; Santo Andika Jaya Sinaga; Tari Nurfadilah; Nurul Azmi; Kusuma Kusuma; Nurita Nurita; Nur Fatihah; Tiorisma Nahampun; Dugarina Mitra Jenuin Parapat; Muhamad Nur Amin; Danyi Aprizal (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
This community service activity was carried out in the Kota Baru District, Bintan Regency, focusing on enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) through packaging design innovation and the implementation of digital marketing using social media and online marketplaces. The main challenges faced by MSMEs in this area are limited digital technology use and poor product packaging quality, which restricts marketing efforts to local consumers. The implementation method involved several stages, including socialization, training, application, and evaluation. During the training phase, MSME actors were provided with knowledge and skills in creating logos, labels, and product packaging designs that are attractive and functional, with an emphasis on aesthetics and practicality to capture consumer attention. In addition, MSMEs were trained to utilize social media and e-commerce platforms such as Shopee, Tokopedia, Facebook, and Instagram to expand their market reach. The results of this activity showed an increase in MSME actors' understanding and skills in designing safer, more appealing packaging that aligns with market trends, as well as their ability to market products digitally. The application of attractive packaging strategies and digital marketing has proven to be effective in enhancing product appeal, expanding market segmentation, and driving sales growth. Therefore, this program provides a tangible contribution to empowering MSMEs in the Kota Baru District, supporting the development of a sustainable local economy, and opening up broader market opportunities.